Analgesic efficacy of low-dose intrathecal neostigmine in combination with fentanyl and bupivacaine for total knee replacement surgery - Amit Jain; Kajal Jain; Neerja Bhardawaj (Wolters Kluwer Medknow Publications, 2012)
Background and Aim: Intrathecal (IT) neostigmine has been used as an adjunct to spinal anesthesia. The purpose of this study was to determine whether a combination of low-dose neostigmine IT would enhance analgesia of a fixed dose of fentanyl IT, in patients undergoing unilateral total knee replacement (TKR) surgery with spinal anesthesia. Settings and Design: Forty-five patients scheduled for unilateral TKR were randomized to one of the three groups (n = 15) and prospectively studied using placebo-controlled, double-blinded design. Materials and Methods: A 19-G epidural catheter was introduced through the L3-L4 interspace with patient in the sitting position, followed by spinal anesthesia administration through the L3-L4 interspace. Fifteen milligrams of hyperbaric bupivacaine (3 ml) plus the test drug (0.5 ml) was administered IT. The test drug was normal saline (0.5 ml) in group I; fentanyl 20 mcg (0.4 ml) and normal saline (0.1 ml) in group II; and fentanyl 20 mcg (0.4 ml) and neostigmine 1 mcg (0.1 ml) in group III. Characteristics of sensory and motor block, heart rate, and blood pressure were recorded intraoperatively. Postoperatively, pain scores, postoperative nausea and vomiting (PONV) scores, and sedation scores, and postoperative analgesic dose were recorded. Results: Forty-five patients were enrolled in this study and 43 patients were subjected to statistical analysis. Overall 24-h visual analog score in group III was significantly less than in those who received fentanyl alone (P = 0.00). The durations of complete analgesia and effective analgesia were longer for all patients in group III compared with group II (P < 0.05) and group I (P < 0.005) patients. The total number of epidural top ups (rescue analgesia) required was less in group II (P < 0.05) and group III (P < 0.005) patients, compared with the control group. The incidence of nausea and vomiting was not increased in group III patients. Conclusions: The addition of 1 mcg neostigmine IT increased the duration of analgesia and decreased the analgesic consumption in 24 h in TKR. There was no increase in the incidence of adverse effects.